The Association Between Dietary Fiber Intake and Central Obesity With Hypertension Among High School Teachers at SMA 1 and SMA 2 Sumenep - Kiptiya, Mariyatul; Jannah, Miftahul; Purnasari, Galih; Amareta, Dahlia Indah (Journal of Public Health for Tropical and Coastal Region, 2025)
Introduction: Hypertension is often referred to as a silent killer because it generally presents without any symptoms or complaints. The number of hypertension cases in Sumenep Regency increased from 70,870 in 2022 to 103,873 in 2023. Central obesity and fiber intake play important roles in hypertension. This study aimed to analyze the association between dietary fiber intake and central obesity with the incidence of hypertension in teachers.Methods: This analytical study used a cross-sectional design. A random sampling method was used to select 68 respondents for this study. A digital sphygmomanometer was used to monitor blood pressure, and a measuring tape was used to measure waist circumference to assess central obesity. Dietary fiber consumption was evaluated using a Semi-Quantitative Food Frequency Questionnaire. Chi-square test was used for statistical analysis.Results: Most respondents were mostly between 25-44 years, were non-smokers, and had no family history of hypertension. Sodium intake was mostly higher than the recommended level, and fiber intake was mostly inadequate. Most of the subjects had central obesity and normotension. The study showed no association between dietary fiber intake and the incidence of hypertension among the teachers (p = 0.248).  There was ans association between central obesity and the incidence of hypertension among teachers (p = 0.006), in which the ones wo had central obesity tended to had hypertension compared to the ones who had no central obesity.Conclusion: Central obesity is associated with hypertension among high school teachers in Sumenep.